Analysing the loyalty levels displayed by football fans: A case study on Cape Town City Football Club - Desai, Muhammed (Marketing, 2018)
According to conventional wisdom, football fans exhibit perpetual loyalty to the clubs that they choose to support. These prevailing beliefs are largely the product of the fanaticism and intense partisanship that fans display. However, in South Africa, the reality is that the majority of the football teams are either failing to harness this loyalty, or that the loyalty levels that their fans display, contradict conventional wisdom. Due to the important role that these fans play in revenue generation, there is a need for leadership at these clubs to better understand this lucrative market. The objective of this study was to establish whether the loyalty levels displayed by fans in South Africa correspond with, or contradict, conventional wisdom. The limited understanding of the matter within a South African context means that clubs lack the required understanding of their respective fan bases. This creates a situation, which stifles the efficacy of management to implement positive changes. This study was anchored in the model of Stewart and Smith (2007) of sport fans' motivations. There are three core dimensions distinguished by the model. These relate to psychological, socio-cultural and social motives, all of which facilitate the process of an individual becoming a fan; and then subsequently remaining loyal. A qualitative research approach was used to collect the data for this study. An interview guide was used to collect the information from the fans and the top management of Cape Town City Football Club through face-to-face interviews. Each interview was recorded with the aid of a voice recorder and all the data collected were then transcribed. The findings from the study show that fans demonstrate more support to Cape Town City Football Club when the team is winning, as opposed to when it is going through a rough patch. Conclusively, the lack of understanding of fans in football clubs means that it is difficult to communicate in an all-inclusive way, considering that not all fans are the same. Based on the findings, the study suggests that leadership at South African football clubs should allow for open dialogues to be created, in which the issues can be discussed; so that practices implemented would better serve the target population.